To free the soul from the body-prison:: the function of true philosophy - Casadesus, Francesc (Revista Archai, 2016)
Plato portrays Socrates, in the last hours in his cell before facing death, as an expert in the hidden details of the Afterlife. He achieves this through the use of mystery terminology, of Orphic-Pythagorean origin, even presenting himself as highly knowledgeable or, even, as an initiate in this domain. However, as usual in many of his dialogues, Plato conveniently transformed this terminology into philosophical concepts. Thus, the notions of the soul’s immortality and initiation are used to define what, on diverse occasions, he calls “correct”, orthos, philosophy. In this context, Plato changed the Orphic metaphor of the body understood as the soul’s tomb, soma-sema, for the image of the body-prison. As I will attempt to show in this paper, this transformation in the metaphor owes to Plato’s interest in rectifying and “improving” the Orphic image of the tomb which, for ethical, epistemological and literary reasons, seemed insufficient to him.